2003
DOI: 10.1023/a:1021725400321
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Examined emotional competence in 87 children, aged 7-10 years, who varied with respect to reports of aggressive behavior to determine whether individual differences in emotional competence characterize children with higher levels of aggressive behavior. Emotional competence was assessed during a 1-hr lab visit that included (a) an observational period consisting of a modified disappointment paradigm, (b) assessment of cognitive and language abilities, and (c) 2 structured emotion interviews. Children with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 18 publications
5
31
0
2
Order By: Relevance
“…Overall, our findings are consistent with previous research that has documented emotion regulation deficits in adolescent anxiety and depression (Bradley 1990, 2000; Cicchetti et al 1995; Bohnert et al 2003; Suveg and Zeman 2004; Southam-Gerow and Kendall 2000). Extant literature, underscoring the transdiagnostic nature of RNT (e.g., Kranzler et al 2016; Mennin and Fresco 2013), as well as emotion dyregulation (Aldao and Nolen-Hoeksema 2010), dovetails nicely with the current hypothesized model.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, our findings are consistent with previous research that has documented emotion regulation deficits in adolescent anxiety and depression (Bradley 1990, 2000; Cicchetti et al 1995; Bohnert et al 2003; Suveg and Zeman 2004; Southam-Gerow and Kendall 2000). Extant literature, underscoring the transdiagnostic nature of RNT (e.g., Kranzler et al 2016; Mennin and Fresco 2013), as well as emotion dyregulation (Aldao and Nolen-Hoeksema 2010), dovetails nicely with the current hypothesized model.…”
Section: Discussionsupporting
confidence: 92%
“…Several theorists have argued that emotion regulation deficits have an important role in the development of psychopathology in adolescents (Bradley 1990, 2000; Cicchetti et al 1995; Bohnert et al 2003; Suveg and Zeman 2004; Steinberg et al 2009). Our current study further substantiates this notion and provides greater specificity about the relationship between particular types of difficulties with emotion regulation and social anxiety and depression (c.f.…”
Section: Discussionmentioning
confidence: 99%
“…To briefly summarize, deficits in the ability to effectively regulate emotions have been implicated in depression (e.g., Silk, Steinberg & Morris, 2003), anxiety disorders (e.g., Southam-Gerow & Kendall, 2000; Suveg & Zeman, 2004), eating disorders (e.g., Sim & Zeman, 2004, 2006), posttraumatic stress disorder (e.g., Cloitre, Koenen, Cohen, & Han, 2002), aggression (e.g., Bohnert, Crnic, & Lim, 2003), ADHD (e.g., Walcott & Landau, 2004), and self-injurious/suicidal behavior (e.g., Nock, Wedig, Holmberg & Hooley, 2008; Selby, Yen, & Spirito, in press). Across these disorders, deficits in emotion regulation have been found to contribute to the development, maintenance, or exacerbation of symptoms.…”
Section: The Transdiagnostic Role Of Deficits In Emotion Regulationmentioning
confidence: 99%
“…ER strategies have been researched mainly in adults, although recent studies have shown their relevance in childhood and adolescence (Betts, Gullone, & Allen, 2009;Gullone, Hughes, King, & Tonge, 2010;Gullone & Taffe, 2012;Larsen et al, 2013), and they have been related to psychological disorders in this population, such as anxiety, depression (i.e., Garber, Braafladt, & Weiss, 1995;Mathews, Kerns, & Ciesla, 2014;Silk, Steinberg, & Morris, 2003;Southam-Gerow & Kendall, 2002;Suveg & Zeman, 2004), aggressiveness (i.e., Bohnert, Crnic, & Lim, 2003;Dearing, Relyea, & Simons, 2002;Muñoz, Kimonis, Frick, & Aucoin, 2013;Sullivan, Helms, Kliewer, & Goodman, 2010) or eating disorders (i.e., Sim & Zeman, 2005, 2006, among others.…”
Section: Introductionmentioning
confidence: 99%